2011
DOI: 10.3809/jvirtex.2011.00268
|View full text |Cite
|
Sign up to set email alerts
|

Melt inclusions in migmatites and granulites

Abstract: Important advances have been made during the last 15 years in the study of melt inclusions in minerals from migmatites and granulites. Pioneer work on high temperature metapelitic anatectic enclaves in peraluminous dacites from SE Spain has shown that droplets of granitic melt can be trapped by minerals growing during incongruent melting reactions, and that the composition of such trapped melts can be representative of that of the bulk melt in the system during the anatexis of the rock. Therefore melt inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 43 publications
5
70
0
Order By: Relevance
“…2 and 4 in Cesare et al, 2009 or Fig. 7 in Cesare et al, 2011) in peritectic garnet in xenolithic granulites and migmatites (Cesare et al, 2009.…”
Section: Melt Inclusionsmentioning
confidence: 97%
See 1 more Smart Citation
“…2 and 4 in Cesare et al, 2009 or Fig. 7 in Cesare et al, 2011) in peritectic garnet in xenolithic granulites and migmatites (Cesare et al, 2009.…”
Section: Melt Inclusionsmentioning
confidence: 97%
“…The glass phase in the melt inclusion represents a peraluminous rhyodacitic Cl-enriched melt phase that was CO 2 saturated in the lower crust (Chupin et al, 2001) indicating the presence of a high-salinity aqueous and a CO 2 -rich fluid. Another example of melt inclusions found in granulite xenoliths includes the ones described by Cesare et al (2009Cesare et al ( , 2011. They identified extremely small glass e and (larger) so-called "nanogranite" inclusions (see Figs.…”
Section: Melt Inclusionsmentioning
confidence: 97%
“…The melt inclusion has a typical polyhedric shape ("negative crystal"; see Cesare et al 2011) and crystallized into a fi negrained aggregate of quartz (Qtz), biotite (Bt), K-feldspar (Kfs), apatite (Ap) and plagioclase (not visible in this image). IMAGE COURTESY OF OMAR BARTOLI, UNIVERSITY OF PARMA, ITALY…”
Section: Figurementioning
confidence: 99%
“…Recent studies have demonstrated that melt inclusions (MI) constitute a new and powerful tool to investigate crustal anatexis (Cesare 2008;Cesare et al 2009Cesare et al , 2011Cesare et al , 2015. Studies of MI in crustal anatectic enclaves found within peraluminous dacites of SE Spain have shown that these trapped droplets of melt, now solidified to glass due to rapid ascent and extrusion, can provide precise information on the composition of primary anatectic melts during, and on the mechanisms of, crustal anatexis (Cesare et al 1997(Cesare et al , 2003Acosta-Vigil et al 2007, 2012a.…”
Section: Introductionmentioning
confidence: 99%